MANAJEMEN KELAS DENGAN PENDEKATAN BEHAVIOR- MODIFICATION APPROACH DAN IMPLEMENTASINYA DALAM PEMBELAJARAN MAHARAT AL KALAM - Amrulloh Khoirul Ma’arif; Muhtarom Muhtarom (Prodi Pendidikan Bahasa Arab Fakultas Agama Islam, 2021)
ABSTRACTTeaching book or text book is compilation of teaching material. Teaching book consider as one of the most important aspect in teaching activity, because it help teachers to design teaching process in class so the main or aim of the teaching can be achieved. This research purpose is to (1) know the process of making teaching book for maharoh qiro'ah (reading skill) based on Tsaqofah Islamiyah (Islamic culture) in Ibnu Sina education campus of Kepanjen Malang. (2) to know the effectiveness of using teaching book or text book. This research is research and development (R and D), the research method used to create a product; teaching book or text book and test it to the research subject after having validation from the experts. The population in this research is all the students semester 3 who take reading 3. The development model is adopted from Moelenda model with 5 steps of ADDIE (Analysis, Design, Development, implementation, evaluation)Key Words: development, text book for maharoh qiro’ah, Islamic Culture